Prevalence of syphilis and HIV infection during pregnancy in incarcerated women and the incidence of congenital syphilis in births in prison in Brazil - Rosa Maria Soares Madeira Domingues; Maria do Carmo Leal; Ana Paula Esteves Pereira; Barbara Ayres; Alexandra Roma Sánchez; Bernard Larouzé (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: This study aimed to estimate the prevalence of syphilis and HIV infection during pregnancy, the mother to child transmission of syphilis and the incidence of congenital syphilis in incarcerated women in Brazil; to compare these rates to those observed in pregnant women outside of jail; and to verify the maternal factors associated with syphilis infection during pregnancy in free and incarcerated women. We used data from two nationwide studies conducted during the period 2011-2014. The Birth in Brazil study included 23,894 free women cared for in 266 hospitals. The Maternal and Infant Health in Prisons study included 495 incarcerated pregnant women or mothers living with their children, according to a census conducted in 33 female prisons. The same case definitions and data collection methods were used in both studies. The chi-square test was used to compare the characteristics of incarcerated and free women with a significance of 0.05. For incarcerated women, the estimated prevalence of syphilis during pregnancy was 8.7% (95%CI: 5.7-13.1) and for HIV infection 3.3% (95%CI: 1.7-6.6); the estimated mother to child transmission of syphilis was 66.7% (95%CI: 44.7-83.2) and the incidence of congenital syphilis was 58.1 per 1,000 living newborns (95%CI: 40.4-82.8). Incarcerated women had a greater prevalence of syphilis and HIV infection during pregnancy, lower quality of antenatal care and higher levels of social vulnerability. Syphilis infection showed to be an indicator of social vulnerability in free women, but not in incarcerated women. Health initiatives in prison are necessary to reduce healthcare inequalities and should include adequate antenatal and birth care.